Sosialisasi Penerapan Sistem Informasi Desa (SID) Berbasis Teknologi Informasi Dan Komunikasi (TIK) Di Desa Pitra Tabanan - Parasari, Nyoman Sri Manik; Purnama, Adi; Maheswari, AA Istri Agung (STMIK Royal, 2024)
The lack of public awareness and knowledge about technological advances, especially the Village Information System and the use of information and communication technology is the main problem of Pitra Tabanan Village. Most bureaucratic activities in Pitra Village are still carried out conventionally. Villagers continue to use strategic conventions for everything from information dissemination to administration and even data collection. Therefore, we initiated counseling, education, and mentoring programs for Village Information Systems Based on Technology, Information, and Communication. This activity program aims to introduce transparent, effective, and efficient work systems and methods. The people of Pitra Village are increasingly aware of the importance of technological progress as a result of this work program. because it helps and relieves conventional human work. It is hoped that this ICT-based village information system can serve as an example for Pitra Village to continue to develop and develop into a more advanced community and village. keywords : socialization, information and technology systems, village development